ANALYSIS OF GOOD MANUFACTURING PRACTICE AT HOME INDUSTRY FOR CATFISH FLOSS IN PURWOSARI, KEDIRI REGENCY - Susetyo Ilman Rosyadi; Eddy Afrianto; Achmad Rizal; Rusky Intan Pratama (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This study aims to study the application of Good Manufacturing Practice (GMP) at home industry for catfish floss in Purwosari, Kediri Regency. This research was conducted in May 2017, located in Purwosari Village Kandat Subdistrict Kediri Regency and Fisheries Processing Laboratory of Padjadjaran University. Laboratory testing was conducted at the Laboratory of Testing Services Faculty of Agricultural Industrial Technology Padjadjaran University and Laboratory of Control and Testing of Quality of Fishery Products of East Java. The method used is survey, by observing directly the flow of process for making catfish floss. Organoleptic testing with 20 semi-trained panelists. Based on the results of the research, the process of making catfish abon is the acceptance of materials, washing I, weeding, washing II, steaming, shredding, mixing, frying, slicing, packaging, storage and loading (no pressing process). Microbiological test (ALT Aerob: 1.7 x 102 Colonies / g, E. coli: <3 APM / g, Staphyloccocus aureus: <10 Colonies / g, Salmonella negative), chemical test (protein: 40.55% and air water: 4.83% ) and organoleptic test (7,2) according to SNI specification. Catfish floss is good in the specified quality specification, but there needs to be improvement in the processing process so that catfish floss can provide quality assurance and safety to the consumer.